Optimization and Bioactive Evaluation of Bifurcaria bifurcata Antioxidant-Rich Extracts for Functional Food and Pharmaceutical Applications - Aurora Silva; Maria Carpena; Lucia Cassani; Clara Grosso; Paula Garcia-Oliveira; Cristina Delerue-Matos; Jesus Simal-Gandara; Maria Fatima Barroso; Miguel A. Prieto (MDPI AG, 2024)
In recent years, consumers have been increasingly interested in natural, healthier, functional foods, with a focus on sea-based products such as algae. Bifurcaria bifurcata (BB) is a macroalga that belongs to the Phaeophyceae class. These brown algae are recognized as the source of bioactive molecules of great interest to the pharmaceutical and nutraceutical industries. The present work applied response surface methodology to optimize the microwave-assisted extraction of the poorly studied algae. The optimization variables were time, pressure, and solvent composition (ethanol/water) and the response parameters selected were yield, total phenolic and flavonoid content, and the antioxidant profile by evaluating DPPH•+, ABTS•+ scavenging activity, and β-carotene discoloration capacity. The results obtained reveal remarkable bioactivity of the crude extract of BB with positive results as an antioxidant and antimicrobial agent. Furthermore, the BB extract's capacity to inhibit enzymes related to neurodegenerative diseases and its anti-inflammatory and anti-proliferation activity open the possibility of future food or pharmaceutical applications.